(untitled) (Journal of the College of Basic Education, 2022)
The research has dealt with setting standards for central admission in Iraqi universities and institutes for the purpose of determining the student’s intentions, capabilities, and preparations, which enables him to choose his specialization, which he will join quietly and away from the emotions, confusion, hesitation, anxiety, and desire followed in the current central admission procedures.